PROCESS MAPPING IN A LOGISTICS COMPANY - Hudáková, Martina (2023)
This diploma thesis aims to explain business process management in the context of logistics companies, along with process mapping and modeling. The theoretical part supports the practical part, where processes of chosen organisation are mapped using semi-structured in depth interview method for data collection, followed by creation of AS-IS process models. Furthermore, it is followed by value-added analysis of said processes in order to determine the possibility for their automation, which is supported by creation of TO-BE process models. These models are further supplemented with recommendations for their further implementation.